MENINGKATKAN HASIL BELAJAR SEJARAH DENGAN MENGGUNAKAN APLIKASI KAHOOT DI KELAS XII IPA 4 MAN ASAHAN - Rosi, Mehawani (Jurnal Analisis Pendidikan Sosial, 2024)
The background of this research is the the weakness of history educators in maxime creativity, and use of internet technology, especially the E-Learning application as a learning medium, especially history learning in the classroom. The use of information technology in distance education learning during this pandemic is very important, because learning is currently done online. The purpose of this journal is to find out the learning outcomes of students by using the Kahoot application in history learning. The existence of the Kahoot learning media is expected to be one way to improve students' historical thinking skills and can erode the impression of boring, monotone, uninteresting, rigid, just like that and with good learning outcomes. Kahoot is an online evaluation tool as an enrichment in the classroom. The purpose of this study was to obtain learning outcomes using an android-based quiz with the Kahoot application in the classroom with the material for the Indonesian Nation's Struggle in Maintaining the Integration of the Indonesian Nation in Maintaining the Integration of the Nation and the Republic of Indonesia.